2006
DOI: 10.1259/bjr/36530782
|View full text |Cite
|
Sign up to set email alerts
|

A review of current local dose–area product levels for paediatric fluoroscopy in a tertiary referral centre compared with national standards. Why are they so different?

Abstract: A prospective single centre study has been performed to assess dose-area product (DAP) values in children having fluoroscopic examinations and to revise local diagnostic reference levels (DRLs). DAP measurements for 2658 examinations performed in a dedicated fluoroscopy room over a period of 21 months were analysed. Data for the eight most commonly performed examinations (2215 cases) are presented. DAPs (75th centile) for upper gastrointestinal studies and micturating cystograms are substantially lower (by a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 6 publications
0
9
1
Order By: Relevance
“…Fluoroscopic screening time is of limited use as a measurement of radiation dose, as radiation time depends on a number of technical parameters such as radiation beam energy, intensity, orientation, field size and skin source distance. This makes the radiation time a very poor comparative metric to estimate radiation dose [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopic screening time is of limited use as a measurement of radiation dose, as radiation time depends on a number of technical parameters such as radiation beam energy, intensity, orientation, field size and skin source distance. This makes the radiation time a very poor comparative metric to estimate radiation dose [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that our results were approximately 60% higher than other studies. This may be explained by the fact that the body size affects the dose received, and it seems better to assign patients to narrower age groups, that will not have an unduly large range of body weight and size (Hiorns et al, 2006). Besides this, too little number of patients was investigated in this study, which means that each procedure may change significantly the 75th percentile.…”
Section: P Ka Values and Comparison Among Present Study And Literaturementioning
confidence: 97%
“…P KA values have been estimated for pediatric barium meal examinations according to patient weight and age Chapple et al, 1992Chapple et al, , 1998Martin et al, 1994;Ruiz et al, 1996;Canevaro et al, 2004;Chateil et al, 2004;Hiorns et al, 2006;Damilakis et al, 2006;Dimitriadis et al, 2011;Emigh et al, 2013;Wambani et al, 2014;Yakoumakis et al, 2014;Hart et al, 2009). However, in Brazil, no diagnostic reference levels (DRLs) have been established for fluoroscopy-guided examinations.…”
Section: Introductionmentioning
confidence: 99%
“…This allowed to see the difference in dose delivered at different points along the field. The spirit level purpose was to ensure tube head is perpendicular to sensitive window of detector while tape measure and meter rule were used to measure SID in both the projected field and standard field at recommended SID [11].…”
Section: Literature Reviewmentioning
confidence: 99%